أثر المزيج التسويقي للتعليم العالي على إختيار الطلبة للجامعات الأجنبية: طرح نموذج مفاهيمي تجريبي .: The impact of the marketing mix of higher education on students’ choice of foreign universities: An experimental conceptual model. - عبد اللطيف معامير; عيسى بولخوخ; محمد لوشن (Journal of North African Economies, 2025)
Competition among international universities has increased the demand for enrollment of students in various universities of higher education that offer different programs in the field of higher education, especially those that offer postgraduate programs. This study aims to investigate a new concept in terms of marketing mix of higher education through the assignment of students' choices for foreign universities. We presented the conceptual model of the study, which was tested by the SEM method. This study was conducted among 140 Algerian students wishing to study in a foreign university following the experimental approach. The study showed that the marketing mix of higher education affected the selection processes of foreign universities through reputation, guide, price, promotion.